2001
DOI: 10.1095/biolreprod65.6.1726
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Follicular Fluid and Serum Share a Unique Isoform of Matrix Metalloproteinase-2 That Is Degraded by the Oviductal Fluid1

Abstract: Whereas the mammalian fertilization environment consists of possible products of the mutual interaction between oviductal and follicular fluids in addition to both fluid components, little is known regarding the interaction. In the present study, we have demonstrated that a mutual interaction occurs, resulting in the biochemical changes of follicular fluid components. Gelatin zymographic analyses of bovine follicular fluid (bFF) showed consistently a distinct, gelatinolytic activity having a molecular weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Gelatin zymography revealed that some of the gelatinase bands are common to serum/follicular fluid and ULF, some are uterus‐specific, and others are pregnancy‐specific. The 84 and 60 kDa gelatinase bands of serum and follicular fluid detected in the present study are similar to the 84–88 and 62 kDa gelatinases reported in bovine follicular fluid (Kim et al, 2001). In the absence of CaCl 2 , the activity of 60 kDa gelatinase band increased with the progress of the estrous cycle with highest activity in follicular stage ULF, whereas in the presence of CaCl 2 , the activity of this band decreased with the progress of the estrous cycle with highest activity in early luteal stage ULF (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…Gelatin zymography revealed that some of the gelatinase bands are common to serum/follicular fluid and ULF, some are uterus‐specific, and others are pregnancy‐specific. The 84 and 60 kDa gelatinase bands of serum and follicular fluid detected in the present study are similar to the 84–88 and 62 kDa gelatinases reported in bovine follicular fluid (Kim et al, 2001). In the absence of CaCl 2 , the activity of 60 kDa gelatinase band increased with the progress of the estrous cycle with highest activity in follicular stage ULF, whereas in the presence of CaCl 2 , the activity of this band decreased with the progress of the estrous cycle with highest activity in early luteal stage ULF (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our findings, Kim et al. () detected two gelatinase bands of 97 and 62 kDa in bovine OF. The authors suggested that based on its molecular weight, the 62 kDa form could correspond to MMP‐2.…”
Section: Discussionsupporting
confidence: 94%
“…; Kim et al. , ). MMP and TIMP oviductal functions remain elusive although it is well known that this system is involved in several aspects of the ovarian and uterine function (Curry and Osteen ).…”
Section: Introductionmentioning
confidence: 98%
“…Non-esterified fatty acids are suggested to be introduced in the oviductal lumen via two pathways: (1) a rather small fraction through the ovulation of a NEFAcontaining follicle [55] and (2) a larger fraction through the natural formation of the OLF, which is essentially an ultrafiltrate from the blood [41]. Preliminary data from our laboratory have suggested a close correlation between serum NEFA concentrations and these in the OLF, making the effects of alternating unidirectional NEFA exposure but also bidirectional exposure physiologically relevant to study.…”
Section: Discussionmentioning
confidence: 99%